Blast syndrome - pathophysiology, diagnosis and treatment of blast injuries - Havlová, K; Doležel, R; Hána, L; Pohnán, R (Rozhledy v chirurgii, 2023)
The incidence of explosions in large agglomerations is high even during peacetime and continues rising. Blast syndrome injuries are complex, with shock wave causing severe injuries of multiple organ systems. In situations with large numbers of injured persons, effective triage allows an early diagnosis and treatment of the highest number of victims. Treatment is challenging, and potentially conflicting therapeutic goals may alternate. This review provides an overview of the pathophysiology of blast injuries, current diagnostic algorithms and therapeutic procedures.
Keywords: Blast Injuries; Explosions; poranění tlakovou vlnou; Incidence; lidé; explosion; treatment; exploze; incidence; type 2 diabetes; multiple injuries; blast syndrome; Humans